Probing the 17F+p potential by means of elastic scattering at near barrier energies - Patronis, N.; et al., ... (HNPS Advances in Nuclear Physics, 2019)
Results from the first stage of analysis of the recently performed 17F+p experiment are presented. The experiment was performed at the EXOTIC facility of Legnaro National Laboratory (Italy, LNL-INFN), where the 17F radioactive beam is available. The measurement of elastic scattering angular distributions, in a wide angular range (θcm=20-160 deg) was taken over in order to probe the potential at two near barrier energies, namely: 3.5 AMeV and 4.3 AMeV. The present work, should be considered as the starting point of a general survey along drip line nuclei, aiming to a better understanding and mapping of the nuclear potential at near barrier energies.